Optimasi HPMC K15M, Karbopol 940, dan Propilen Glikol pada Formula Nanoemulgel Naringenin Metode D-Optimal Mixture Design - Rakhmi Hidayati; Opstaria Saptarini; Ilham Kuncahyo (Fakultas Farmasi Universitas Setia Budi, 2022)
Naringenin is a flavanone from citrus fruit which has antioxidant activity which has low bioavailability in water. The way to increase the bioavailability of naringenin is to create a SNEDDS delivery system. Nanoemulsion preparations are considered to be comfortless to use due to low viscosity, dispersibility and stability. To solve this problem, SNEDDS is combined into a gel base known as nanoemulgel. The nanoemulgel formed is optimized using D-Optimal Mixture Design method. The aim of this study are determining the combination of HPMC K15M, carbopol 940 and propylene glycol in the optimal nanoemulgel naringenin formula. Naringenin is made into SNEDDS formulation, determined by the hydrogel base formula design: HPMC K15M, carbopol 940, and propylene glycol and obtained 16 formulas. The formed naringenin SNEDDS is dispersed in hydrogel and optimization of viscosity, dispersion, adhesion, cumulative percent of naringenin using franz diffusion cells and stability test are carried out. The data is analyzed on the D-Optimal Mixture Design method using Software Design Expert Version 12. The optimum proportions on a hydrogel base are HPMC K15M of 2%, carbopol 940 of 0.50%, and propylene glycol of 2.50% can have an effect on the critical parameters of viscosity of 3996 cp, dispersion of 5.80 cm, adhesion of 63.39 seconds, and the cumulative percent of naringenin penetration test of 26,54%.